Stock market trends and oil prices: Evidence from a developing country - Indrawati Yuhertiana; Corry Natasha Patrioty; Nafsiah Mohamed (Contemporary Economics, 2019)
This study examines the influence of oil prices, business size, and return on equity investment, market liquidity, systematic risk and portfolio investment on the Indonesian stock market. The main dependent variables of this stock market study are the four dimensions of stock market efficiency, stock market return, stock market valuation and stock market volatility. Data were gathered over the 2008-2016 period with annual observations for 30 firms currently listed in Indonesian financial markets. A two-fold regression analysis is applied. First, the impacts of explanatory variables on stock market indicators and oil prices is examined through a separate regression technique. Next, the lagged values of oil prices are added to the model to reflect their empirical influence on stock market measures. The study findings indicate that oil prices significantly affect all the performance indicators of the Indonesian stock market. Market liquidity also has a significant impact on the stock market. When the lagged predictors of stock market efficiency, stock market valuation, and stock market volatility were added, they were found to be significantly associated with the first lag of oil prices. These findings provide important justification of the literature on financial markets and their behavior when oil prices change. However, the study is limited with respect to other economic variables whose effects on the stock market is not observed. Future studies can address this constraint by taking the GDP, inflation, interest rates, and interaction of regional financial markets as core determinants of the local stock market in Indonesia.
Keywords: 330; Stock market efficiency; oil price volatility; Indonesia; financial market; GDP